환대서비스 종사원의 ESG 경영인식이 고객지향성, 진정성, 경영성과 간의 구조적 관계 - 전용택(Yong-Taik Chun); 이정은(Jung-Eun Lee) (무역연구, 2024)
Purpose – This study aims to use it as an opportunity to examine ESG management as well as identify the structural relationship between customer orientation, sincerity, and management performance among hospitality service employee ESG management awareness. Design/Methodology/Approach – To achieve the research purpose, theoretical and empirical research were conducted in parallel. The empirical study was conducted through a survey targeting employees working at hotels, family restaurants, coffee shops, and fast food restaurants, and the results were presented. Findings – A hypothesis was established, and as a result of hypothesis testing, a significant relationship was formed between ESG management awareness and customer-oriented behavior. The relationship between ESG management awareness and sincerity formed a significant relationship, and the relationship between customer orientation and management performance formed a significant relationship. A significant relationship was also formed between authenticity and management performance. Research Implications – Since the hospitality service industry is based on human resources, the role of employees as the foundation is important because it goes beyond customer satisfaction and creates customer return visits. Therefore, changes in job performance, including changes in the roles and abilities of employees, are important. There must be changes in the systems and environmental characteristics inside and outside the company. Moreover, it is believed that the high performance that employees are responsible for and the corporate environment have a significant relationship with management performance, and further influence each individual to take initiative in innovative behavior. KCI Citation Count: 3